Estimating the Number of Immigrants in Spain: An Indirect Method Based on Births and Fertility Rates - Rosero Bixby, Luis (2011)
This article proposes an indirect method to validate existing estimates of immigrants’ stock from the Spanish municipal population register, which some believe might be over-counting immigrants who double register in different municipalities or fail to deregister when leaving the country. The proposed method uses two pieces of information: births to immigrants and their fertility rates. Data on births by parents’ origin come from the Spanish birth registry; fertility rates are estimated with data from the 2007 National Immigrant Survey. For female immigrants, the indirect estimate does not differ signifi cantly from the count in the register, which can be taken as a validation of both sources. Among men, however, the population register counts 15% more immigrants than the indirect estimate, and this difference is statistically signifi cant. Western European men and women, and Romanian men are immigrant groups with substantial and statistically signifi cant excess count in the population register compared to this article’s estimate. The opposite pattern, i.e. ratio of register-toestimated number of immigrants lower than one, is found for Ecuadorian men and women and African men, suggesting that these groups might be under-counted in the population register, although the observed differentials are not statistically significant.